2020
DOI: 10.1055/a-1101-9783
|View full text |Cite
|
Sign up to set email alerts
|

Index aus Diameter der Vena cava inferior und Aorta abdominalis bei Neugeborenen – eine praxisrelevante Methode zur Erfassung einer Hypovolämie

Abstract: ZusammenfassungBei kranken Neugeborenen steht häufig eine Hypovolämie im Vordergrund der klinischen Probleme. Eine effiziente, schonende Diagnostik ist für eine adäquate Therapie entscheidend. Sonografische Untersuchungen entsprechen diesen Anforderungen. Um die Volumensituation der Kinder zu beurteilen, wird eine Relation aus Durchmessern der Vena cava inferior (IVC) und der Aorta abdominalis (Ao) erfasst. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…9 In another study undertaken to predict hypovolemia in small-for-gestational-age and large-for-gestational-age newborns using the IVC/Ao index, the index was found to be significantly smaller in the former, compared with the measurement performed on the first day after birth. 10 In the current study, in which we evaluated the IVC/Ao index in the FGR cases, we found similar results between the groups. The reason why the IVC/Ao index was similar in our study may be a result of the decrease in both the IVC diameter and the aortic diameter in the intrauterine period.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…9 In another study undertaken to predict hypovolemia in small-for-gestational-age and large-for-gestational-age newborns using the IVC/Ao index, the index was found to be significantly smaller in the former, compared with the measurement performed on the first day after birth. 10 In the current study, in which we evaluated the IVC/Ao index in the FGR cases, we found similar results between the groups. The reason why the IVC/Ao index was similar in our study may be a result of the decrease in both the IVC diameter and the aortic diameter in the intrauterine period.…”
Section: Discussionsupporting
confidence: 79%
“…In a study conducted in Nigeria, the IVC/Ao index was reported to be beneficial in determining the degree of dehydration and the optimal treatment modality in children 9 . In another study undertaken to predict hypovolemia in small‐for‐gestational‐age and large‐for‐gestational‐age newborns using the IVC/Ao index, the index was found to be significantly smaller in the former, compared with the measurement performed on the first day after birth 10 . In the current study, in which we evaluated the IVC/Ao index in the FGR cases, we found similar results between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations